Strategi Komunikasi Humas Polres Musi Rawas Dalam Meningkatkan Citra Institusi Di Masyarakat - Ngatiyah, Chusnul; Yunus, Muhammad; Khasanah, Nevi Laila (STAI Bumi Silampari, 2023)
Public relation is a form of public service, if poor public service practices by state officials result in the communitys needs not being met, which ultimately does not bring about general welfare. Poor public services occur because of the bad intentions of state administrators to abuse their power and authority, therefore there is a need for a strategy in building the identity of the Musi Rawas Police. The communication strategy developed by Musi Rawas Police Public not only in obtaining a good image, but also in how the positive image that has been built can be maintained. The type of research used is a qualitative approach with the approach regarding public relation. Data collection techniques use observation methods, interview methods, and documentation. The implication of this research is that it is hoped that the public Relations Communications Strategy in building the image of institutions in society will be maximized, because it is necessary to create good relations between the police and the community.